THE EFFECTIVENESS OF TEACHING ENGLISH VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE STORYTELLING (TPRS) - Nurlaili Nurlaili; Siti Nurani; Larisa Yohana (Deiksis, 2015)
This present research aims at analyzing the effectiveness of Total Physical Response Storytelling (TPRS) method in teaching English Math-shape vocabularies. The research was carried out in Madrasah Ibtidaiyah Sirojul Banat Jakarta by using the experiment method. There were 31-first grade literate students as samples chosen by purposive sampling technique. The data is gathered by using the test instrument with one-group pretest-posttest design. The data was analyzed by using t-test formula. Findings have shown that Total Physical Response Storytelling (TPRS) method is said to be effective applied in teaching English math-shape vocabularies which is identified by the enhancement of students’ comprehension toward the vocabularies’ meaning as well as the increase of their motivation and creativity experiencing the learning process more actively and interactively.Keywords: vocabulary teaching, storytelling technique, TPRS